2020
DOI: 10.1021/acs.est.0c00156
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Immobilization of Cr(VI) Species in Long-Term Tannery Waste Contaminated Soils

Abstract: Chromium speciation in naturally contaminated soils appears more complex than spiked studies have shown. This study characterized Cr speciation (oxidation states; availability; molecular geometry) intended to highlight the genesis of immobile Cr(VI) species in long-term tannery waste-contaminated soils. In a series of samples obtained from Shuitou in China, chemical extraction methods showed that Cr(III) was dominant(>96.7% of total Cr), with Cr(VI) concentration up to 144 mg kg −1 . Of the total Cr(VI) presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(4 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…As shown in Fig. S20, the distribution of Cr was overlapped with soil mineral ions (Al and Ca) on the biochar surface, probably due to the complexation of chromate with mineral ions, immobilization of Cr on newly formed minerals (Shi et al 2020), or co-precipitation into new minerals (Mullet et al 2007).…”
Section: Changes In the Reducing Capacity Of Biochar For Cr(vi) Reduc...mentioning
confidence: 99%
“…As shown in Fig. S20, the distribution of Cr was overlapped with soil mineral ions (Al and Ca) on the biochar surface, probably due to the complexation of chromate with mineral ions, immobilization of Cr on newly formed minerals (Shi et al 2020), or co-precipitation into new minerals (Mullet et al 2007).…”
Section: Changes In the Reducing Capacity Of Biochar For Cr(vi) Reduc...mentioning
confidence: 99%
“…The researchers point out that the device is field-deployable and thus the accuracy of determination of the separated species at a later time is unaffected by any interconversion that may occur during transport and storage. To study Cr speciation in soils contaminated by tannery waste, Shi et al 111 applied (a) US EPA method 3060A (alkaline extraction) and US EPA method 7196A (spectrophotometry with DPC), and (b) synchrotron-based XANES and spatially resolved XRF. The XANES results indicated that a significant portion of the Cr VI , was not removed by the phosphate buffer extraction, and the XRF maps showed that Cr was associated with both Mn and Fe.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
“…It shows excellent performance in the removal of cations (e.g., Cs + , Ca 2+ , Sr 2+ , and Ra 2+ ) from aqueous media. It is generally believed that coprecipitated ions are not released unless the host mineral is dissolved. Thus, coprecipitation with barite or other minerals is expected to function as a cost-effective method to immobilize long-lived radionuclides and is a promising tool to remove toxic and/or radioactive elements from polluted solutions.…”
Section: Introductionmentioning
confidence: 99%